Spatial and social inequalities among young people: Looking for ‘site effects’ - Tavares, I.; Carmo, R. M. (Journal of Youth Studies)
This study explores the relationship between spatial and social inequalities affecting young people. The objective is to analyse this relationship considering the circumstances of young people and to ascertain to what extent favourable social conditions associated with living in the most relevant and dynamic cities are an expression of ‘site effects’. The study is based on a questionnaire with responses from over 5000 young people. In order to gain a more profound understanding of the spatial and social inequalities experienced by young people, both inferential statistics and a logistic regression model were employed. The findings suggest that when the socio-spatial dimension is given due consideration, inequalities are observed to deepen in terms of the different social backgrounds that continue to determine many young people's paths. The process of peripheralisation of territories contributes to the maintenance of structural inequalities between denser, more urbanised cities and those living in more peripheral areas. The results reveal the existence of ‘site effects’, showing a strong relationship between young people’s access to the country's most important cities and their social background.